Spatiotemporal Evolution Law of Precipitation in Zhengzhou City Based on Multi-Source Data - JIANG Xi (Renmin Zhujiang)
The rise of precipitation data products provides new ideas for research in the field of hydrology and meteorology, as well as a strong data basis for hydrological forecasting and water resource management in areas lacking data. As an important supplement to station data, the accuracy of precipitation data products is crucial for runoff simulation, hydrological measurement and calculation, etc. In recent years, rainstorm events have occurred frequently in Zhengzhou City, and the number of ground rainfall stations is few, which fails to help hydrometeorologists make decisions. In this study, four sets of precipitation data products, namely, China Meteorological Forcing Dataset (CMFD), Integrated Multi-satellitE Retrievals for GPM Final Run (GPM IMERG), ECMWF Reanalysis V5 (ERA5), and Global Satellite Mapping of Precipitation (GSMaP), were evaluated through quantitative indicators and classification indicators, and the precipitation data suitable for Zhengzhou City was screened out. The slope analysis method and MK test method were used to reveal the spatiotemporal evolution law of precipitation in Zhengzhou City. The results show that four types of satellite precipitation products have achieved good application effects in Zhengzhou City, with CMFD performing the best overall. All four sets of precipitation data show an overestimation of light rain and an underestimation of moderate and heavy rain. In terms of space, the overall performance of the four sets of precipitation data in the southwest region of Zhengzhou City is better than that in the northeast region. The precipitation in Zhengzhou City shows a non-significant decrease in terms of time, with a decreasing rate of about 0.2 mm/a. In terms of space, it shows a decreasing trend from southwest to northeast.